Stem Cell Banking - Ilic, Dusko (Stem Cell Biology and Regenerative Medicine,, 2014)
This volume explores changing global perspectives in banking of cord blood, mesenchymal, embryonic and induced pluripotent stem cells for clinical use. The book is divided into two parts: The first part examines topics including the setting of standards for pluripotent stem cell banking and regulation and ethical issues in stem cell banking. The second part delves into stem cell banking efforts in countries including Japan, Switzerland, India and Iran, among others.  Implementing core values and common standards depend often on specific circumstances of political and economic setting, which makes flexibility as important as systematic planning. Banking of stem cells is not just building a repository and storing samples. The planning, design, construction and maintenance involve multiple skilled professionals. Stem cell banks are points where technology and medicine converge with ethics, laws and regulations. If properly designed and organized, their utilization will have a broad impact not only on the scientific community and medical professionals but also on the general public.  .